High‐Performance Perovskite Light‐Emitting Diode with Enhanced Operational Stability Using Lithium Halide Passivation. (29th January 2020) - Wu, Tian; Li, Junnan; Zou, Yatao; Xu, Hao; Wen, Kaichuan; Wan, Shanshan; Bai, Sai; Song, Tao; McLeod, John A.; Duhm, Steffen; Gao, Feng; Sun, Baoquan
Abstract: Defect passivation has been demonstrated to be effective in improving the radiative recombination of charge carriers in perovskites, and consequently, the device performance of the resultant perovskite light‐emitting diodes (LEDs). State‐of‐the‐art useful passivation agents in perovskite LEDs are mostly organic chelating molecules that, however, simultaneously sacrifice the charge‐transport properties and thermal stability of the resultant perovskite emissive layers, thereby deteriorating performance, and especially the operational stability of the devices. We demonstrate that lithium halides can efficiently passivate the defects generated by halide vacancies and reduce trap state density, thereby suppressing ion migration in perovskite films. Efficient green perovskite LEDs based on all‐inorganic CsPbBr3 perovskite with a peak external quantum efficiency of 16.2 %, as well as a high maximum brightness of 50 270 cd m −2, are achieved. Moreover, the device shows decent stability even under a brightness of 10 4 cd m −2 . We highlight the universal applicability of defect passivation using lithium halides, which enabled us to improve the efficiency of blue and red perovskite LEDs. Abstract : Grünes Licht : Eine grüne Perowskit‐Leuchtdiode mit hoher Effizienz und Langzeitstabilität wurde durch den Passivierungseffekt von Lithiumbromid hergestellt. LiBr passiviert effektiv die Oberflächendefekte, was zu einem hohen Anteil strahlender Rekombination führt. Blaue und rote Perowskit‐LEDs können ebenfalls durch Passivierung mit Lithiumhalogeniden (LiX) hergestellt werden. CB: Leitungsband, VB: Valenzband.